Obtenção e caracterização de compósito verde de casca de pinhão e poliuretana derivada do óleo de mamona - Protzek, Giuliana Ribeiro (2017)
Polymeric composites reinforced with natural fibers are denominated green composites. Polymers comes from petroleum source, a non-biodegradable material and has volatile organic compounds, VOC, in its composition. Organic solvent are toxics and pollute the environment. The Polyurethane derived from castor oil is polymer produced from renewable sources, biodegradable material and there are no VOC in its composition. Araucária pine nut shell is a residue from its Araucaria pine seed. The aim of this work is to develop and characterize composites of pine nut shell with polyurethane derived from castor oil. The fiber was chemically characterized, thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). PU was characterized by flexural strength, FTIR and TGA and composites was characterizes by density test, water absorption and swelling in thickness, flexural strength, FTIR, TGA. SEM evaluated the fracture surface and X-ray and vertical density profile verified the composites homogeneity. 35%PU composites presented flexural strength of 51,55 MPa, density of 1018 kg/m³, 7,95% of 24h water absorption and 5,36% of 24h swelling in thickness of. The material exhibits properties suitable for use in furniture and handicrafts.